2012
DOI: 10.1152/ajpregu.00636.2011
|View full text |Cite
|
Sign up to set email alerts
|

Loss of muscle strength during sepsis is in part regulated by glucocorticoids and is associated with reduced muscle fiber stiffness

Abstract: Sepsis is associated with impaired muscle function but the role of glucocorticoids in sepsis-induced muscle weakness is not known. We tested the role of glucocorticoids in sepsis-induced muscle weakness by treating septic rats with the glucocorticoid receptor antagonist RU38486. In addition, normal rats were treated with dexamethasone to further examine the role of glucocorticoids in the regulation of muscle strength. Sepsis was induced in rats by cecal ligation and puncture, and muscle force generation (peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…[6,7] Moreover, differences between limb muscles are also reported in rodent experimental models of sepsis with a pronounced decrease in muscle strength and release in myofilaments in glycolytic compared to oxidative skeletal muscles. [5,8,9] Altogether, these data highlight that skeletal muscles are differently impacted by systemic inflammation during sepsis depending on function, contractile activity, and metabolic profile. However, the underlying molecular mechanisms remain poorly understood.…”
Section: Introductionmentioning
confidence: 78%
“…[6,7] Moreover, differences between limb muscles are also reported in rodent experimental models of sepsis with a pronounced decrease in muscle strength and release in myofilaments in glycolytic compared to oxidative skeletal muscles. [5,8,9] Altogether, these data highlight that skeletal muscles are differently impacted by systemic inflammation during sepsis depending on function, contractile activity, and metabolic profile. However, the underlying molecular mechanisms remain poorly understood.…”
Section: Introductionmentioning
confidence: 78%
“…Among them, many pathological conditions are associated with increased circulating levels of glucocorticoids (GCs), which cause muscle atrophy. Recent studies have shown that sepsis-induced muscle atrophy is induced by a reduction in function of the cross-bridges between actin and myosin, which is at least partially regulated by GCs [4].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Chronic infection has been linked to compromised diaphragm function in animal models 8 and human patients. 9 Respiratory failure in CF is caused by parenchyma destruction, recurrent infection, and bronchiectasis, and respiratory muscle dysfunction might also play a critical role. Respiratory muscle compromise in CF can lead to respiratory muscle fatigue and thus contribute to respiratory failure.…”
Section: Introductionmentioning
confidence: 99%